Insights Into Adolescents' Substance Use in a Low–Middle-Income Country During the COVID-19 Pandemic - Sen, Lee Thung; Siste, Kristiana; Hanafi, Enjeline; Murtani, Belinda Julivia; Christian, Hans; Limawan, Albert Prabowo; Adrian,; Siswidiani, Levina Putri (Frontiers in Psychiatry, 2021)
Introduction: The COVID-19 pandemic and its lockdown has been a significant life event for many individuals, particularly adolescents. The immense psychological pressure could drive risky behavior, e.g., substance use, while lockdown might lead to decreased use. This study aimed to observe the change in substance use among adolescents in Indonesia and the moderating variables to consumption during the COVID-19 lockdown period. Methods: This study utilized an online survey from April 28th to June 30th, 2020. The hyperlink was disseminated to school administrators and parenting groups through social media and direct messages. A total of 2932 adolescents (17.4±2.24 and 78.7% females) submitted valid responses. The survey was comprised of sociodemographic, substance use details, and psychometric sections, including AUDIT, CDS-12, SDQ, and PSQI. Results: Overall, adolescent alcohol use during the pandemic was 5.1%, cigarette smoking was 3.1%, and drug consumption was 0.4%. Over half (53.4%) of alcohol drinkers reported increased drinking and 33.1% had harmful or dependence-like drinking behavior; in contrast, 44.4% of adolescent smokers disclosed reduced cigarette consumption. Around 37.8% of the drug users indicated increased use. During the pandemic, adolescent alcohol use was associated with higher education (AOR= 2.67, 95% CI 1.02-4.86, p= .04), higher AUDIT scores (AOR= 1.33, 95% CI 1.25-1.42, p< .001), and very low prosocial behavior (AOR= 2.46, 95% CI, 1.52-3.88, p< .001). Cigarette smoking was correlated with male sex (AOR= 9.56, 95% CI 5.64-16.62, p< .001), age (AOR= 1.40, 95% CI 1.14-1.75, p< .001), and higher CDS score (AOR= 1.17, 95% CI 1.13-1.20, p< .001). Conclusions: Rates of adolescent substance use were significant, with sizeable proportions reporting higher usage. This appeared to occur predominantly in specific demographics and those with a lower protective psychosocial attribute, i.e., prosocial behavior, during the lockdown. These findings should urge the strengthening of adolescent addiction care during and after the pandemic.